2019
DOI: 10.1088/1742-6596/1339/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Active learning in scientific writing skill using Indonesian textbook based on character education

Abstract: The purpose of this study was to describe development of text-based and character-based Indonesian textbook model. The method was research and development which consists of four stages, they are: (1) Exploration, (2) Model Development, (3) Model Testing, and (4) Disemination. The research approach in the exploration stage was qualitative descriptive approach. Data collection was done through in-depth interviews, observation, documentation, and questionnaires. Data analysis technique was done by interactive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results showed that students' skills in writing improve with the use of active learning techniques and methods. St and Winarni (2019) explored the development of an Indonesian textbook model based on text and character and the impact of active learning on students' writings. The study used the qualitative descriptive approach.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The results showed that students' skills in writing improve with the use of active learning techniques and methods. St and Winarni (2019) explored the development of an Indonesian textbook model based on text and character and the impact of active learning on students' writings. The study used the qualitative descriptive approach.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Guidebooks are media/tools in the form of books that contain principle procedures and descriptions of basic materials for use by educators (Suryaman, 2012). The material in the guidebook can be in the form of theories related to the development of professional duties of educators (Slamet et al, 2019). Guidebooks are considered media that meet the needs because they succinctly contain the information needed by guidance and counselling teachers.…”
Section: Introductionmentioning
confidence: 99%